Environmental health, environmental education and health promotion in Colombia. Are they in the same way? - Arevalo Bernal, Oscar Eduardo
This article seeks to analyze the performance of strategies in the field of Environmental Education and Health Promotion within Environmental Health in Colombia. For this, a brief list of international antecedents on the matter and applicable legal regulations on the matter was made; Progress in related public policies was reviewed based on technical reports from state entities and the opinion of selected authors after a bibliographic review; and finally a discussion of the results found is established. In conclusion, despite the important regulatory advances in the matter, there are still several challenges to ensure that Environmental Education and Health Promotion are implemented in a comprehensive manner from Environmental Health management. Among them are intersectoral action, the adequate implementation and evaluation of the public policies developed and the lack of participation of different actors in society.